(3JMaI GdCdHGH hfNHI GdEYLGHs - (3GHf CHj GdQHjY , eMeO Hf YHO GdQMje Hf SdjeGf GdeGRfj GdbS GdCfOdSj GdZRfGWj, CHh YHO Gddg,J (B565 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY GdYGde Ydi JhMjOg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B199 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B158s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B477 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B81 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs